2008
DOI: 10.1364/ao.47.000422
|View full text |Cite
|
Sign up to set email alerts
|

Design and initial performance of SHARP, a polarimeter for the SHARC-II camera at the Caltech Submillimeter Observatory

Abstract: We have developed a foreoptics module that converts the Submillimeter High Angular Resolution Camera generation II (SHARC-II) camera at the Caltech Submillimeter Observatory into a sensitive imaging polarimeter at wavelengths of 350 and 450 m. We refer to this module as "SHARP." SHARP splits the incident radiation into two orthogonally polarized beams that are then reimaged onto opposite ends of the 32 ϫ 12 pixel detector array in SHARC-II. A rotating half-wave plate is used just upstream from the polarization… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 28 publications
0
45
0
Order By: Relevance
“…Polarisation analysis of the 620.701 GHz maser components Linear polarisation measurements are often optimised to determine the Stokes Q and U parameters independently from each other (Li et al 2008;Hezareh & Houde 2010). If we define four intensity measurements I ϕ within the equatorial system with ϕ set to 0 • when pointing north and increasing eastwards, then…”
Section: Hifi Observations At 620701 Ghzmentioning
confidence: 99%
“…Polarisation analysis of the 620.701 GHz maser components Linear polarisation measurements are often optimised to determine the Stokes Q and U parameters independently from each other (Li et al 2008;Hezareh & Houde 2010). If we define four intensity measurements I ϕ within the equatorial system with ϕ set to 0 • when pointing north and increasing eastwards, then…”
Section: Hifi Observations At 620701 Ghzmentioning
confidence: 99%
“…The understanding of the physical phenomena responsible for polarized interstellar emission provides valuable information about the underlying astrophysical processes, an important example being the formation and evolution of stars. Since the 1990s, polarimetry techniques and instruments have been developed for a wide range of wavelengths, from optical (e.g., Magalhaes et al 1996;Wiktorowicz & Matthews 2008) to the submillimeter and radio regimes (e.g., Platt et al 1991;Hildebrand et al 1997;Shinnaga & Tsuboi 1999;Greaves et al 2003;Li et al 2008;Thum et al 2008;Hildebrand et al 2009;Houde et al 2009;Heiles 2001;Heiles et al 2001aHeiles et al , 2001b.…”
Section: Introductionmentioning
confidence: 99%
“…Refers to shortest wavelength for polarimeters with several bands. References: (1) Platt et al (1991), (2) Schleuning et al (1997), (3) Dowell et al (1998), (4) Holland et al (1999), (5) Greaves et al (2003), (6) Dowell et al (2003), (7) Li et al (2008), (8) Krejny et al (2008), (9) (Aumont et al 2010, 27 fwhm) and JCMT/SCUPOL (Matthews et al 2009, 20 fwhm) are shown for comparison.…”
Section: Discussionmentioning
confidence: 99%